Trade Barriers in Activity Analysis - Reiter, S. (Review of Economic Studies, 1952)
Journal Article Trade Barriers in Activity Analysis Get access S. Reiter S. Reiter Standford, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 3, 1952, Pages 174–180, https://doi.org/10.2307/2295887 Published: 01 January 1952